ÁDEBIYAT SABAQLARÍNDA INTERAKTIV TEXNOLGIYALAR - - ұлт ұстазы, Ахмет Байтұрсынов; Гүлшат Бекхожаевна, Қалтеева (Scientific Impulse, 2023)
The article describes the methods of using interactive technologies in teaching Karakalpak literature, features of the use of lectures and methodological issues of their teaching.